MACROFLORAL ANALYSIS OF FOUR PRIVIES FROM LOT 39, KLONDIKE GOLD RUSH NATIONAL HISTORICAL PARK, SKAGWAY, ALASKA - Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
Fill from four privies on Block 39 at Klondike National Historical Park in Skagway, Alaska, were sampled for macrofloral remains. The lots on which these privies sit were occupied from about 1897 until the late 1920's. Before 1910, Skagway was existing as a gold-rush town and a supply center for the interior. After 1910, the population declined and stabilized at around 500 people. Because privy deposits provide more direct evidence of foods consumed, macrofloral analysis of the fill from the four privies is used to determine foods eaten by the privy users and to provide information concerning use of indigenous and introduced plant resources and possible variation in household consumption.